Combined quantum tunnelling and dielectrophoretic trapping for molecular analysis at ultra-low analyte concentrations - Longhua Tang (Nature Portfolio, 2021)
Probes that effectively utilize quantum tunneling are sought after for high-resolution study of nanoscale objects. Here the authors present an easily fabricated probe of two nanoelectrodes that enables highly sensitive quantum-tunneling-based sensing of single molecules.